(untitled) (Biological Sciences - PJSIR, 2005)
This paper presents the results obtained on the kinetic study of non-oxidative dissolution of natural galena in aqueous hydrochloric acid with the addition of sodium chloride. A chemical reaction on the surface of galena controlled the dissolution rates under the experimental conditions of investigation. The galena dissolution rate was of the first order with respect to hydrochloric ion activity in hydrochloric acid solution. The addition of sodium chloride to the acid solution greatly enhanced the dissolution rate. The effect of sodium chloride has two possible interpretations: firstly, it may be the result of an increase in the hydrogen ion activity; secondly, the enhancement of the dissolution rate, observable at the high sodium chloride concentration, may be due to the specific absorption of chloride ions or the surface complexing of chloride ions on galena surface